Zircon fission track and U-Pb dating methods applied to São Paulo and Taubaté Basins located in the southeast Brazil - Curvo, E. A C [UNESP]; Tello S., C. A. [UNESP]; Carter, A.; Dias, A. N C [UNESP]; Soares, C. J. [UNESP]; Nakasuga, W. M. [UNESP]; Resende, R. S. [UNESP]; Gomes, M. R. [UNESP]; Alencar, I.; Hadler, J. C. (Elsevier, 2013)
Zircon samples from the Cenozoic São Paulo and Taubaté Basins and Mantiqueira Mountain Range (southeast Brazil) were concomitantly dated by zircon Fission Track Method (FTM) and in situ U-Pb dating method. While FTM detrital-zircon data are ideally used to provide low-temperature information, U-Pb single detrital grain ages record the time of zircon formation in igneous or high grade metamorphic environments. This methodology may be used to study the possible sources of the basins sediments. The results suggest that the São Paulo Basin is composed of sediments from just one source, the Mantiqueira Mountain Range. On the other hand, the Taubaté Basin presents further sediment sources besides the Mantiqueira Mountain Range. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Basin; Fission-track; Source to sink study; U-Pb; Zircon; Fission track; Low temperatures; Sediment sources; Source to sinks; Southeast Brazil; Zircon fission tracks; Fission reactions; Geochronology; Landforms; Lead; Sedimentology; Sediments